2012
DOI: 10.1097/mao.0b013e31825367a5
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of a Commercially Available Cochlear Implant Processor With Dual-Microphone Beamforming

Abstract: The results of the study suggest that the Nucleus 5 sound processor provides significantly better speech recognition in quiet and in noise when compared with performance with the Nucleus Freedom processor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 31 publications
1
46
2
Order By: Relevance
“…Cochlear implant manufacturers provide several technologies to improve performance in noise. Directional microphones, advances in signal processing, and use of remote-microphone hearing assistance technology (HAT) have been shown to improve speech recognition in noise (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Cochlear implant manufacturers provide several technologies to improve performance in noise. Directional microphones, advances in signal processing, and use of remote-microphone hearing assistance technology (HAT) have been shown to improve speech recognition in noise (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…SmartSound incorporated a range of input processing technologies including automatic sensitivity control, channel- specific adaptive dynamic range optimization, and both moderately directional and adaptive directional microphones (Patrick et al, 2006). A further release called SmartSound2 in the Nucleus ® 5 system included an additional highly directional microphone technology (Wolfe et al, 2012). The most recent release, SmartSound iQ in the Nucleus 6 system, additionally includes an automatic scene classifier, a CI specific background noise reduction technology, and a wind noise reduction technology.…”
mentioning
confidence: 99%
“…A third was a new fixed highly directional microphone called zoom, which had a super-cardioid pattern providing 20-dB free-field attenuation at 120°. One study comparing the Nucleus 5 zoom directional microphone to the Freedom Standard and Nucleus 5 Standard directional microphones showed SRT improvements of 8.6 and 7.8 dB respectively (Wolfe et al, 2012). CI users wishing to utilize different microphone polar patterns for different noise situations could use either the processor or a remote assistant to manually change programs.…”
mentioning
confidence: 99%
“…1B). In a comparative study using the identical sound processor for a group of cochlear implant users, Wolfe et al (7) found similar results, although a comparison between electric and acoustic stimulation must be limited in its conclusions. They observed significantly improved speech recognition in quiet of 3.1% at 60 dBA with the CP810 compared with the Freedom when both are used in the Everyday program.…”
Section: Discussionmentioning
confidence: 87%
“…Since the release of the DACI, a new generation of sound processor, the Nucleus CP810 Sound Processor (Cochlear Ltd., Sydney, Australia), has become available for cochlear implants. This new sound processor has shown a significant improvement in speech recognition in quiet and noise in cochlear implant patients in comparison to the previous processor (7) (Freedom Sound Processor [Cochlear Ltd.]). When the Nucleus CP810 became available for acoustic implants we hypothesized that the new sound processor would provide a similar improvement in acoustic stimulation with the DACI.…”
mentioning
confidence: 99%